1994
DOI: 10.1108/02651339410067012
|View full text |Cite
|
Sign up to set email alerts
|

Ethnocentric Tendencies, Marketing Strategy and Import Purchase Behaviour

Abstract: Reports on an analysis of the relative importance of various marketing mix strategies and consumer ethnocentric tendencies in the decision to purchase imports undertaken via a nationwide mail survey of personal computer owners in the USA. The results indicate that ethnocentric tendencies are able to explain a much greater amount of variation in purchase behaviour than marketing mix variables. Concludes that the inclusion of ethnocentric tendencies into future studies on origin bias appears to be warranted give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 34 publications
(40 reference statements)
3
61
0
7
Order By: Relevance
“…Ethnocentric customers tend to evaluate positively the products which belong to their own group and negatively the products that are not. Ethnocentric customers will tend to reject people, symbols and values of different cultures because their cultural objects are their pride (Herche, 1994). The ethnocentric behavior based on group boundaries is usually defined by one or more of observable characteristics such as religion.…”
Section: Religio-centric Positional Advantage (Rpa)mentioning
confidence: 99%
“…Ethnocentric customers tend to evaluate positively the products which belong to their own group and negatively the products that are not. Ethnocentric customers will tend to reject people, symbols and values of different cultures because their cultural objects are their pride (Herche, 1994). The ethnocentric behavior based on group boundaries is usually defined by one or more of observable characteristics such as religion.…”
Section: Religio-centric Positional Advantage (Rpa)mentioning
confidence: 99%
“…Accordingly, factors other than product quality may help to explain the phenomenon. Several factors have been identified, such as brand globalness (e.g., Steenkamp et al, 2003), consumer ethnocentrism (e.g., Shimp and Sharma, 1987;Herche, 1994;Klein, 2002), cultural openness (e.g., Sharma et al, 1995), global openness (e.g., Suh and Kwon, 2002), and product judgment (e.g., Han, 1988;Knight, 1999;Kaynak and Kara, 2002). However, the majority of these studies have been undertaken in advanced economies.…”
Section: Introductionmentioning
confidence: 99%
“…These ethnocentric tendencies are better predictors of purchase behavior than demographic or marketing mix variables. Herche (1994) also found that ethnocentric consumers tend to reject people, symbols and values that are culturally different, while inner cultural objects will become recipients of pride and attachment.…”
Section: Literature Reviewmentioning
confidence: 97%